IMMEDIATE EFFECT ON MANUAL DEXTERITY IN A CHILD WITH DOWN SYNDROME PRE AND POST GAMETHERAPY SESSION: CASE REPORT (CIPEEX, 2025)
Objective: To analyze the immediate effect of gametherapy on the manual dexterity of a child with Down Syndrome in a single session. Methodology: The present study involves a 15-year-old child with Down Syndrome, selected according to the established inclusion criteria. Initially, screening will be carried out using an identification form, where all inclusion and exclusion criteria will be analyzed. Subsequently, the participant will undergo assessments at the Human Movement Analysis Laboratory (LAAMH) of UniEVANGÉLICA. Results: It is expected that the patient submitted to gametherapy will present superior results compared to the control group, reflected in the improvement of manual dexterity. Conclusion: This study demonstrates that gametherapy is a promising intervention for improving motor coordination and manual dexterity in children. The analyses revealed significant changes in the evaluated variables, confirming the effectiveness of the approach and suggesting its potential for integration into pediatric rehabilitation programs. These findings expand the knowledge on the use of innovative technologies in child rehabilitation but also establish a solid foundation for future investigations, aiming to optimize therapeutic care in pediatric populations.
Keywords: Children with Down Syndrome; Gameterapy; Reaching movement; Manual dexterity